Analysis Performance for Evaluation of Schedule Irregularities on Bore Pile Foundation with FTA - Melvin Melvin; Andri Irfan Rifai; Amanatullah Savitri (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: In construction projects, delays are disruptive and expensive. Therefore, the reason for the schedule delay needs to be identied. The delay factors determined in previous research were predominantly studied through surveys. In these studies, the participants were a stakeholder in construction projects, and the reason for schedule lateness was identied through their point of view. Design/methodology/approach: This research is conducted at a bored pile project in Opus Apartment, Batam, Indonesia. The studies are done through the Fault Tree Analysis method to find the root causes of the delay. Findings: Causes of delay in construction to prevent lateness on future construction projects. Research limitations/implications: Evaluation of delay causes on the bore pile foundation project in Opus Apartment. Practical implications: Evaluation of lateness in construction project through Fault Tree Analysis Paper type: Case Study